Chemical analysis of Gaula river water and adjoining hill side tension crack water near Amiya village, Nainital - Singh T.N.; Goswami S.K.; Sharma P.K.; Sharma Y.C. (My University, 2025)
Gaula river is a very important river and caters to the needs of local people in Amiya village, Nainital. People use water of this river for drinking, all domestic applications , irrigation, etc. Authors have made some efforts to assess the water quality of this river by assessing various parameters, namely. pH, and the ionic species Ca2+, Mg2+, Na +,K+,SO42-,Cl- and HCO3. Generally pH of the water from tension crack was higher than that of the river water. Samples from the river showed calcium in 30.28-35.25, magnesium in 8.36-8.49, sodium in 8.87-9.06, potassium in 4.0-4.8, sulphates in 17.7-18.6, chlorides in 4.75-4.88, and bicarbonate ions in 117.3-125.2 ppm ranges. The quality of the water from both the sources was more or constant and unpolluted. The water can be consumed for any purpose without any treatment. © 2006 - Kalpana Corporation.